2020
DOI: 10.1302/0301-620x.102b7.bjj-2019-1590.r1
|View full text |Cite
|
Sign up to set email alerts
|

2020 John Charnley Award: The antimicrobial potential of bacteriophage-derived lysin in a murine debridement, antibiotics, and implant retention model of prosthetic joint infection

Abstract: Aims Current treatments of prosthetic joint infection (PJI) are minimally effective against Staphylococcus aureus biofilm. A murine PJI model of debridement, antibiotics, and implant retention (DAIR) was used to test the hypothesis that PlySs2, a bacteriophage-derived lysin, can target S. aureus biofilm and address the unique challenges presented in this periprosthetic environment. Methods The ability of PlySs2 and vancomycin to kill biofilm and colony-forming units (CFUs) on orthopaedic implants were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…Our study has several limitations. Although we have made every effort to develop a clinically relevant PJI model (28,29,63) and our findings are aligned with published studies of human PJI, (62,64) it will be important to compare our findings to human PJI in greater detail. To this effect, we have initiated a study of human PJI subjects that to date has confirmed low-level T-cell infiltration, but greater heterogeneity and variability in duration of infection before surgical intervention will necessitate a long enrollment period.…”
Section: Discussionsupporting
confidence: 72%
“…Our study has several limitations. Although we have made every effort to develop a clinically relevant PJI model (28,29,63) and our findings are aligned with published studies of human PJI, (62,64) it will be important to compare our findings to human PJI in greater detail. To this effect, we have initiated a study of human PJI subjects that to date has confirmed low-level T-cell infiltration, but greater heterogeneity and variability in duration of infection before surgical intervention will necessitate a long enrollment period.…”
Section: Discussionsupporting
confidence: 72%
“…Bacteriophage therapy has generated interest for many decades, and recent studies have investigated it as an adjuvant in the treatment of osteomyelitis 174 . For example, in a murine model of implant-associated osteomyelitis, the use of a combination of systemic and locally applied bacteriophage-derived lysin (PlySs2), aimed at targeting both planktonic and biofilm-associated bacteria, improved S. aureus infection eradication after debridement and implant retention 175 . Phage therapy has been used for topical delivery in humans for indications such as diabetic toe ulcers and limited cases of other lower extremity osteomyelitis; however, these studies involved small patient numbers without control groups 133 .…”
Section: Synovial Fluidmentioning
confidence: 99%
“…One possible way to circumvent this would be to apply enzybiotics systemically, although this faces its own hurdles. A recent study using the PlySs2 endolysin against an in vivo model of prosthetic joint infection found little significant reduction in CFU numbers in the infected bone following intraperitoneal injection of the lysin, demonstrating that systemic administration does not necessarily ameliorate bone treatment [57]. Systemic lysin administration has always faced the hurdle of rapid renal clearance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed the effectiveness of lysostaphin application via a hydrogel to prevent the onset of S. aureus ODRI [56]. In a separate study, the application of the endolysin PlySs2 was effective in combination with vancomycin in treating an in vivo model of staphylococcal prosthetic joint infection [57]. We, therefore, set out to explore whether an enzybiotic combination specifically tailored for its efficacy in vivo could be effective in treating established ODRI.…”
Section: Introductionmentioning
confidence: 99%